Comparison of Safety and Efficacy of Laparoscopic Pyelolithotomy versus Percutaneous Nephrolithotomy in Patients with Renal Pelvic Stones: A Ran¬domized Clinical Trial - Basiri, Abbas; Tabibi, Ali; Nouralizadeh, Akbar; Arab, Davood; Rezaeetalab, Gholam Hossein; Hosseini Sharifi, Seyed Hossein; Soltani, Mohammad Hossein (Urology Journal, 2014)
Purpose: A randomized clinical trial was designed to compare the efficacy, success rate and surgical complications of percutaneous nephrolithotomy (PCNL) and laparoscopic pyelolithotomy (LP). Materials and Methods: Sixty patients with renal pelvic stones larger than 2 cm were randomly divided into two groups of LP and PCNL. All patients were followed up to three months after surgery using renal diethylenetriaminepentaaceticacid (DTPA) scan and determining the glomerular filtration rate (GFR). Results: Mean operation time (149 ± 31 vs. 107 ± 26 min) and mean hospital stay (3.4 vs. 2.16 days) were significantly higher in LP, but mean hemoglobin drop (0.85 vs. 1.88 g/dL) and the rate of blood transfusion were significantly lower. Stone free rate was 90% and 86.6% for LP and PCNL, respectively (P =.59), while the changes in GFR were not statistically significant 3 days after surgery between two groups. Those in LP group showed better improvement in GFR at three months postoperatively. Improvement of the affected split kidney function was significantly higher in LP group (P =.04). No major complications were observed in both groups according to Clavien grading system. Conclusion: PCNL remains the gold standard treatment for most large kidney stones, nevertheless, laparoscopic pyelolithotomy can be considered for selected cases especially in whom maximal preservation of renal function is necessary.